THE DEBATE ABOUT THE LATIN AMERICAN DEVELOPMENT UNDER THE WAGE-LED AND PROFIT-LED GROWTH REGIMES APPROACH - Fonseca, Pedro Celso Rodrigues; Araújo, Ricardo (Brazilian Keynesian Review, 2023)
This study aimed to identify references to the concepts of wage-led and profit-led growth regime in Latin American structuralist thinking. To do so, we initially review Kaleckian growth models. Then, the following structuralist theses were discussed: the Prebisch's critique of comparative advantage theory, Furtado's stagnationism, and Tavares and Serra's critique of stagnationism. After this analysis, it was possible to realize that, although not formally explicit, references from kaleckian growth regimes are identified in structuralist.